Diagnostic imaging methods applied in long-term surveillance after EVAR. Will computed tomography angiography be replaced by other methods? - Stefaniak, Karolina; Stanisic, Michal; Gabriel, Marcin; Oszkinis, Grzegorz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Endovascular implantation of a stent graft in the abdominal aorta (endovascular aneurysm repair – EVAR) is a widely accepted alternative to open surgery in treatment of abdominal aortic aneurysms. Although EVAR is connected with a significant reduction in the risk of peri- and post-operative complications, it does not eliminate them totally. Long-term surveillance of post-EVAR patients is aimed at early detection of and fast reaction to a group of complications called endovascular leaks. Currently, the gold standard in leak diagnostics is computed tomography angiography (CTA). The other methods are ultrasonography, magnetic resonance (MR) angiography, intra-aneurysm sac pressure measurement, X-ray, and digital subtraction angiography (DSA). Despite many analyses based on long-term research, emphasising the high value and competitiveness of less invasive tests such as US or X-ray compared to CTA, it is still difficult for them to win the trust and acceptance of clinicians. The persisting view is that computed tomography is the test that finally resolves any inaccuracies. Consequently, a patient with a number of concurrent diseases is subject to absurdly high radiation exposure and effects of a radiocontrast agent within a short time. It is therefore logical to acknowledge that the EVAR-related risk is catching up with the open surgery risk, while the endovascular procedure is much more costly. Nevertheless, the status of CTA as the gold standard ultimately seems to be unthreatened. This paper presents a description of the diagnostic imaging tests that make it possible to detect any vascular leaks and to develop strategies for therapeutic processes.